Portfolio based Assessment for teaching English for hotel and tourism - Kurniawan, Ferry; Lustyatie, Ninuk; Usman, Herlina (Edelweiss Applied Science and Technology, 2025)
This study aims to implement and evaluate the use of portfolio-based assessment in teaching English for Hotel and Tourism. In the context of English for Specific Purposes (ESP), portfolio assessment is considered more effective in measuring communicative competence, speaking skills, and the ability to use language in real-life situations commonly found in the hospitality and tourism industry. The research employed a qualitative approach. Instruments such as assessment rubrics, observation sheets, and student reflections were used for data collection. The results revealed that portfolio assessment promotes active student engagement, enhances critical thinking, and allows space for individual language development through reflection. It also enables lecturers to provide more focused and personalized feedback. Therefore, portfolio-based assessment is highly relevant and beneficial for English language instruction in hotel and tourism study programs.